Strategi Pemerintah Kabupaten Badung Dalam Mewujudkan Badung Zero Waste Melalui Program Bank Sampah Sesuai Peraturan Bupati Badung No. 48 Tahun 2018 - Pradhana, I Putu Bayu Fischa Mahaputra Adi; Yashinta, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER, 2023)
Badung as one of the regencies with a dense population in the Province of Bali, has a quite complex of waste problem. Badung Regency has a waste problem which is causing Badung Regency as one of the highest waste contributor in Bali. The waste problem is one of the priorities of the Badung Regency Government to overcome. Realizing the Badung Zero Waste Concept is one of the efforts made by the Badung Regency Government to deal with waste problems, by pursuing a resource-based waste management program through the Garbage Bank. The purpose of this research is to find out the district government's strategy in implementing Badung Regent Regulation No. 48 of 2018 concerning Guidelines for the Implementation of Reduce, Reuse and Recycles through Waste Banks to realize "Badung Zero Waste